(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A benign rare synovial proliferative disease, synovial chondromatosis is characterised through more than one cartilaginous nodules in synovial space. Most commonly affected joint is the knee joint. This is a case report of a male patient of age 18 years presented with right knee joint pain. On radiological assessment using MRI indicates moderate knee joint effusion with synovial thickening and multiple calcified and non-calcified loose bodies were identified. Synovectomy was performed to remove several loose bodies and synovial membrane which was sent to histopathological examination. The results suggest that the procedure, arthroscopy, is an effective diagnostic and therapeutic tool for synovial chondromatosis.